KAJIAN PERILAKU PETANI PEMBUDIDAYA TANAMAN HORTIKULTURA DALAM KONSERVASI LAHAN PADA ZONA AGROEKOLOGI (ZAE) DAERAH ALIRAN SUNGAI (DAS) SERAYU DI WILAYAH KABUPATEN BANYUMAS - Pujiharto Pujiharto (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2009)
This research is aimed at: 1) studying the characteristics of horticultural plants farmers in agroecological zone of Serayu upper catchment area in Banyumas regency, measured by the age, formal education level, job status, the way of farming, farming experience, previous activities before farming, and the level of socio economics in the research area 2) investigating the role of horticultural plants farmers in agroecological zone of Serayu upper catchment area in Banyumas regency in the pattern of land use based on land conservation 3) indentifying the factors that influence the behavior of horticultural plants farmers in agroecological zone of Serayu upper catchment area in Banyumas regency in doing land conservation. The area of Banyumas regency is choosen as the area of research because it has agroecological zone that consists of upper, middle and lower zone along Serayu upper catchment area. Thirty horticultural plants farmers are selected randomly. They are interviewed to get data and information about land conservation behavior. The result of the research shows that the characteristics of horticultural plants farmers in agroecological zone around Serayu upper catchment area are: about 41 – 50 years old, mostly elementary school formal education, farming as the main job, self-farming, 16 – 20 year experience in farming, most of them do not have any previous activities before being farmers and their socio economical level can be categorized as low. The role of horticultural plants farmers in land conservation are: returning residue into the soil (recycling), using organic fertilizer, plant rotation, optimum water management, using high variety plants daptive to specific environment, controlling the pest and disesase by using IPM (Integrated Pest Management) principle, and the balance use of anorganic fertilizer. The factors that influence farmers’ behavior in land conservation are: belief, cultural values orientation, income, land size, attitude and knowledge about conservation. Key words : behavior, horticultural plant farmer, serayu upper catchment area